Metric and differential geometry : The jeff cheeger anniversary volume - Rong, Xiaochun; Dai, Xianzhe (Progress in Mathematics, 2012)
Metric and Differential Geometry grew out of a similarly named conference held at Chern Institute of Mathematics, Tianjin and Capital Normal University, Beijing. The various contributions in this volume cover a broad range of topics in metric and differential geometry, including metric spaces, Ricci flow, Einstein manifolds, Kähler geometry, index theory, and hypoelliptic Laplacian and analytic torsion. The book includes papers on the most recent advances as well as survey articles on new developments. Contributors: M.T. Anderson J.-M. Bismut X. Chen X. Dai R. Harvey P. Koskela B. Lawson X. Ma R. Melrose W. Müller A. Naor J. Simons C. Sormani D. Sullivan S. Sun G. Tian K. Wildrick W. Zhang